Clinical profile of newly diagnosed leprosy patients with special references to deformities and disabilities - Chhakchhuak, Laldinthari; Chhakchhuak, Lalbiakdiki; Rongpi, Rajesh; Lalromawii; George, Sandhya; Balasubramaniyan, Pradeep (Asian Journal of Medical Sciences, 2023)
Background: After leprosy was declared eliminated as a public health problem in India on December 2005, the focus has shifted to the prevention of disability and deformities. This indirectly measures the effectiveness of health education and awareness. Aims and Objectives: This study was conducted to assess the clinical profile and different patterns of disabilities and deformities among newly diagnosed leprosy patients. Materials and Methods: A cross-sectional study was conducted for a period of 1 year on newly diagnosed leprosy patients attending a tertiary care hospital in Kerala. 32 patients included in the study were examined and disabilities observed were graded using WHO disability grading system. The variables are mentioned as numbers and percentages. Results: 50% of the subjects had different grades of deformity/disability (6.25% had Grade 1 disability while 43.75% had Grade 2 disability). The mean duration of disease in patients with and without deformities was 44.19 and 20.5 months, respectively, which was statistically significant (P=0.025). A positive family history of Hansen’s disease was present among 5 (15.63%) patients. The different disability/deformity observed were ulcers, scars, muscle weakness, and redness of eyes. Feet were the most commonly affected site. Conclusion: Proper health education and awareness activities that will promote early recognition of symptoms and reporting are crucial to decrease deformities.